The first formed tooth serves as a signalling centre to induce the formation of the dental row in zebrafish. Issue 1904 (12th June 2019) - Gibert, Yann; Samarut, Eric; Ellis, Megan K.; Jackman, William R.; Laudet, Vincent
Abstract : The diversity of teeth patterns in actinopterygians is impressive with tooth rows in many locations in the oral and pharyngeal regions. The first-formed tooth has been hypothesized to serve as an initiator controlling the formation of the subsequent teeth. In zebrafish, the existence of the first tooth (named 4 V 1 ) is puzzling as its replacement is induced before the opening of the mouth. Functionally, it has been shown that 4 V 1 formation requires fibroblast growth factor (FGF) and retinoic acid (RA) signalling. Here, we show that the ablation of 4 V 1 prevents the development of the dental row demonstrating its dependency over it. If endogenous levels of FGF and RA are restored after 4 V 1 ablation, embryonic dentition starts again by de novo formation of a first tooth, followed by the dental row. Similarly, induction of anterior ectopic teeth induces subsequent tooth formation, demonstrating that the initiator tooth is necessary and sufficient for dental row formation, probably via FGF ligands released by 4 V 1 to induce the formation of subsequent teeth. Our results show that by modifying the formation of the initiator tooth it is possible to control the formation of a dental row. This could help to explain the diversity of tooth patterns observed in actinopterygians and more broadly, how diverse traits evolved through molecular fine-tuning.